Optimal monetary policy in a new Keynesian model with habits in consumption - Campbell Leith; Ioana Moldovan; Raffaele Rossi (European Central Bank (ECB), 2009)
While consumption habits have been utilised as a means of generating a hump shaped output response to monetary policy shocks in sticky-price New Keynesian economies, there is relatively little analysis of the impact of habits (particularly, external habits) on optimal policy. In this paper we consider the implications of external habits for optimal monetary policy, when those habits either exist at the level of the aggregate basket of consumption goods (`superficial' habits) or at the level of individual goods (`deep' habits: see Ravn, Schmitt-Grohe, and Uribe (2006)). External habits generate an additional distortion in the economy, which implies that the flex-price equilibrium will no longer be efficient and that policy faces interesting new trade-offs and potential stabilisation biases. Furthermore, the endogenous mark-up behaviour, which emerges when habits are deep, can also significantly affect the optimal policy response to shocks, as well as dramatically affecting the stabilising properties of standard simple rules.
Keywords: E30; E57; E61; 330; consumption habits; nominal inertia; optimal monetary policy; Geldpolitik; Geldtheorie; Konsumentenverhalten; Preisrigidität; Schock; Neoklassische Synthese; Theorie